ENZYMATIC ANTIOXIDANT RESPONSES TO BIOSTIMULANTS IN CHERRY TOMATO SUBJECTED TO DROUGHT - S. Murtic; R. Oljaca; M. S. Murtic; I. Koleska; A. Muhic (Journal of Animal and Plant Sciences, 2019)
This study was conducted to evaluate the effects of biostimulants on antioxidant enzymes activity in leaves of cherry tomato seedlings (Lycopersicon esculentum Mill. cv. Sakura) under drought conditions. The pot experiment was set in a greenhouse environment at public communal company ’Park’ in Sarajevo. Three biostimulants used in this research were as follows: Bio-algeen S92 (biostimulant made by extracting of seaweed Ascophyllum nodosum (L.) Le Jol.), Slavol (microbial-based stimulant), and Ergonfill (biostimulant obtained by the hydrolysis of proteins of animal origin). Drought induced increases in ascorbate peroxidase (APOD), superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPOD) and pyrogallol peroxidase (PPOD) activities in leaves od seedlings, regardless of biostimulant treatment. The increase in the activities of SOD, APOD, PPOD and GPOD were recorded already at the beginning stage of stress (first day after exposure to stress), while the increase in CAT activity was less pronounced at this phase of stress. The increase in activities of all examined enzymes was significantly slower in leaves of seedlings treated with biostimulants Bio-algeen S92, Ergonfill and Slavol compared to non-treated seedlings under drought conditions, suggesting that the application of these biostimulants contributes to better adaptation of the seedlings to drought.
Keywords: antioxidant; biostimulant; drought; enzyme activity; leaves; stress